Skeletal and dental effects of Class III orthopaedic treatment: a systematic review and meta‐analysis. (30th March 2017) - Rongo, R.; D'Antò, V.; Bucci, R.; Polito, I.; Martina, R.; Michelotti, A.
Summary: To summarise the skeletal, dental and soft tissue effects of orthopaedic treatment on growing skeletal class III patients compared with a concurrent untreated similar control group and to evaluate whether the design of the primary studies may affect the results. A literature search was performed up to the end of February 2016. No restrictions were applied concerning language and appliances. Once the quality score was assessed, a meta‐analysis was performed for the appliances used in more than three studies. A moderator analysis for study design was performed. The level of evidence was evaluated by means of the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) tool. The search resulted in 21 papers. The quality of most of the studies was medium. Each study reported skeletal sagittal improvement and overjet correction. Fourteen studies reported a significant increase in lower facial height. Follow‐up data showed slight relapses in about 15% of patients. Meta‐analyses were performed for the facemask and chin cup. The two appliances were efficient for correcting the sagittal discrepancy, increasing the divergence. In the analysis for study design, the retrospective studies showed a more efficient appliance than RCTs for 6 of 13 variables. The level of evidence was between very low and moderate. There is very low to low evidence that orthopaedic treatment is effective in the correction of Class III skeletal discrepancies and moderate evidence for the correction of the overjet. A common side effect is mandibular clockwise rotation in older subjects.